Cyclical Dynamics and Market Resilience in Global Domestic Tourism: A Multi-Country Analysis of Accommodation Trends and Disruption Patterns - Tunca, Sezai; Balcıoğlu, Yavuz Selim; Cubukcu Cerasi, Ceren; Doganer, Muge; Bayraktar, Umit (Science Publishing Corporation Inc., 2025)
This study investigates cyclical dynamics and market resilience in global domestic tourism using a 28-year UN Tourism dataset encom-passing 12 countries across diverse economic and geographic contexts. Through growth rate analysis, disruption event detection, and resilience indexing, the research identifies 280 distinct economic phases, revealing multi-year cycles marked by gradual expansions (aver-aging 4.2 years) and shorter, sharper contractions (averaging 2.1 years). Three major disruption events—the 2001 crisis, the 2008–09 financial collapse, and the 2020–21 COVID-19 pandemic—demonstrate tourism’s systemic vulnerability, with synchronized declines across domestic markets. While the pandemic caused the steepest declines (31.4%), early recovery was faster than previous crises, under-scoring the impact of adaptive policies and domestic demand shifts. Resilience assessment highlights substantial variation: Finland and Poland exhibited strong growth, low volatility, and rapid recovery, whereas small, tourism-dependent economies such as Cyprus and Liechtenstein faced high instability and prolonged recoveries. These findings advance tourism literature by distinguishing multi-year cycles from long-term growth trends, elucidating disruption transmission effects, and operationalizing resilience through quantitative metrics. The study offers practical implications for policymakers and industry stakeholders, emphasizing diversification, governance quality, and adaptive planning as key levers for mitigating volatility. By reframing domestic tourism as a dynamic, cyclical system, this research contributes to evidence-based strategies for building sustainable and shock-resistant tourism markets. © 2025 Elsevier B.V., All rights reserved.
Keywords: cyclical dynamics; domestic tourism; global disruption; recovery patterns; resilience